Advanced Load Balancing Based on Network Flow Approach in LTE-A Heterogeneous Network. (20th May 2014) - Jia, Shucong; Li, Wenyu; Zhang, Xiang; Liu, Yu; Gu, Xinyu
Abstract : Long-term evolution advanced (LTE-A) systems will offer better service to users by applying advanced physical layer transmission techniques and utilizing wider bandwidth. To further improve service quality, low power nodes are overlaid within a macro network, creating what is referred to as a heterogeneous network. However, load imbalance among cells often decreases the network resource utilization ratio and consequently reduces the user experience level. Load balancing (LB) is an indispensable function in LTE-A self-organized network (SON) to efficiently accommodate the imbalance in traffic. In this paper, we firstly evaluate the negative impact of unbalanced load among cells through Markovian model. Secondly, we formulate LB as an optimization problem which is solved using network flow approach. Furthermore, a novel algorithm named optimal solution-based LB (OSLB) is proposed. The proposed OSLB algorithm is shown to be effective in providing up to 20% gain in load distribution index (LDI) by a system-level simulation.